PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) TERHADAP KEMAMPUAN PENALARAN ADAPTIF MATEMATIS SISWA - Nopitasari, Dian (Universitas Wiralodra, 2016)
This research was conducted in one of junior high school in Tangerang academic year 2015/2016. Aimed to analyze the effect of CPS model on the students’ mathematical adaptive reasoning skills. The method used in this study was a quasi experimental method with randomized posttest only control group design. Samples were obtained as many as two classes by cluster random sampling technique. Based on result of hypothesis this show that students’ mathematical adaptive reasoning skills who were taught by creative problem solving model was higher than the students’mathematical adaptive reasoning skills of those who were taught by conventional model